Bifurcation percutaneous coronary intervention of left main trunk treated using a proximal optimizing technique and proximal balloon edge dilation technique. Issue 1 (January 2022) - Kume, Teruyoshi; Koto, Satoshi; Sudo, Yasuyuki; Hiroshi, Okamoto; Yamada, Ryotaro; Imai, Koichiro; Koyama, Terumasa; Tamada, Tomoko; Neishi, Yoji; Uemura, Shiro
Abstract: We present a case of bifurcation percutaneous coronary intervention (PCI) of the left main trunk (LMT) using a proximal balloon edge dilation (PBED) technique following a proximal optimizing technique (POT). The procedure of the PBED technique entailed precise positioning of the balloon for SB dilation, with the proximal radiopaque marker lying in the cross-sectional plane of the stent struts at the left circumflex artery (LCx) ostium. The PBED technique might prevent stent deformation induced by side branch (SB) dilation and eliminates the need for the second POT procedure in the re-POT sequence. In fact, three-dimensional reconstruction of optical coherence tomography (3D-OCT) revealed good opening of stent cells overlying the LCx ostium without deformation of stent struts causing incomplete stent apposition at the site opposite the LCx, so the second POT procedure was unnecessary in this case. <Learning objective: This is the first case report to describe bifurcation PCI of the LMT using POT-PBED procedures under 3D-OCT guidance. POT-PBED procedures might offer excellent acute results for cross-over single-stent implantation in LMT bifurcation lesions and could eliminate the second POT procedure in the re-POT sequence.>